LES DIFFÉRENDS FRONTALIERS OUGANDO-CONGOLAIS : Un nœud gordien de la coopération bilatérale ou nouvel enjeu de conflit régional ? - Justin Bahinduka Bessisa (IJRDO - Journal of Social Science and Humanities Research, 2019)
The Democratic Republic of Congo (DRC) and Uganda, two countries of the Great Lakes region, share a long border that encourages fluxes of all nature. During last years, this border limit was not revealed that a space of exchange. On the other hand, it nourished the tensions that took the exploding shapes that raised the veil on border disputes between the two countries. In spite of will displayed by the parts to solve these conflicts peacefully, some security incidental is not stopped. This article interrogates stakes of the persistence of these conflicts and the factors that nourish them. It uses itself, besides, to analyze the impact of these conflicts on the cooperation between the two States and propose some tracks of reflection in view of the resolution efficient of these conflicts.